Pengembangan Metode Pengamanan Data Menggunakan Teknik Interpolasi antar Piksel dan Reduced Difference Expansion - Lidya Amalia Rahmania; Tohari Ahmad (Jurnal Rekayasa Elektrika, 2017)
In this globalization era, the internet has been the main media which everyone used to exchange information, from the public such as sport to top secret such as military data. Hence, the requirement of data hiding method called steganography is rising. Steganography is hiding the secret information into another media so that it could be transferred publicly, but only the authorized users could access it. There were two main problems in the data hiding technique: the capacity of the secret and the quality of the generated stego data. In this proposed method, we combined digital image processing called interpolation, used it to predict the new pixel value to hide the secret bit in purpose to increase the bit data capacity with the consequence the reduction of the stego image quality. The experimental result showed that the capacity has increased from that of the previous research.